How to Be A Professional Physical Therapist - Muhfiyatul Ummu (Indonesian Journal of Health Care Management, 2023)
Compared to other health care professions such as medicine, nursing and pharmacy, there is little research has been carried out to examine the nature of practice errors in occupational and physical therapy and often these events have a moral dimension that disturbs the therapists involved, there is no specific standardization regarding service issues in interprofessional physical therapy personnel but is found in several journals discussing cases of analysis related to the principles ethical principles and code of ethics. Not only skills that must be emphasized as physical therapists also need to improve knowledge, skills, abilities, and professional behavior, therefore various collaborative forms of improvement related to ethical codes and professional behavior in physical therapists will be described.